Numerical diagnostics of fluctuation spectrum in 3D magnetic configurations. (30th August 2018) - Kasuya, N.; Nunami, M.; Tanaka, K.; Yagi, M.
Abstract: Numerical diagnostics using 3D simulation data are carried out to capture fluctuation properties in helical plasmas. Here, ion-temperature-gradient (ITG) turbulence data are used and obtained by the gyrokinetic code, GKV-X, with realistic magnetic configuration. Fluctuations are calculated in the field aligned coordinates, which have long wave lengths in the magnetic field direction and are anisotropic in the radial and poloidal directions; their features are represented in the experimental frame. For the validation, the density fluctuation spectrum is calculated, which is integrated along the line of sight as in the phase contrast imaging signals. From that integrated signal, its vertical profile is reconstructed by utilizing the variation of the direction of the magnetic field, as the operation carried out in experimental data. In experiments, there usually exists a limitation on the observation region and spatial resolution, so differences between the deteriorated and real spectra is confirmed by numerical simulations with variations related to spatial limitations. ITG modes have a characteristic wavelength and frequency, and are identified with sufficient spatial resolution even from the integrated signal by comparing the wavenumber spectra at different radial positions. Combination of multiple flux-tube data is also tested for calculation to give fluctuations spreading in wider radial ranges of plasma. These fluctuation spectra are compared with the experimental one for comprehensive understanding of experimental observations.